2011
DOI: 10.1093/jpepsy/jsr002
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Maternal Depressive Symptoms, Maternal Involvement, and Diabetes Management Across Adolescence

Abstract: Mothers' depressive symptoms may undermine her care-giving effectiveness during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 28 publications
3
63
2
1
Order By: Relevance
“…Although previous research finds parental involvement remains high for mothers with depressive symptoms (Wiebe et al, 2011), the relation between depressive symptoms and involvement may depend on the type of parental involvement in disease care. For example, direct parental involvement that includes maternal responsibility for disease management tasks may remain high in mothers with depressive symptoms because mothers may lack the initiative or ability to transfer care to their adolescents (Wiebe et al, 2011). In contrast to direct parental involvement, indirect involvement entails parental monitoring that is less “hands-on” and consists of supervision of diabetes care tasks.…”
mentioning
confidence: 78%
“…Although previous research finds parental involvement remains high for mothers with depressive symptoms (Wiebe et al, 2011), the relation between depressive symptoms and involvement may depend on the type of parental involvement in disease care. For example, direct parental involvement that includes maternal responsibility for disease management tasks may remain high in mothers with depressive symptoms because mothers may lack the initiative or ability to transfer care to their adolescents (Wiebe et al, 2011). In contrast to direct parental involvement, indirect involvement entails parental monitoring that is less “hands-on” and consists of supervision of diabetes care tasks.…”
mentioning
confidence: 78%
“…Mothers with higher level of depressive symptoms tend to provide lesser support and warmth, potentially leading to lower psychosocial adjustment of the child and adolescent 41,42 . Paternal and maternal stress is also related to depressive symptoms in adolescents with T1D 43 .…”
Section: Parental Mental Healthmentioning
confidence: 99%
“…37 One additional family factor that has been found to significantly impact adherence among youth with type 1 diabetes is maternal psychological functioning, including separation anxiety and depression. 16,39 Maternal caregivers, who demonstrate difficulties with separation anxiety and attachment issues with their adolescents, are hypothesized to also have difficulties with their adolescent's eventual need for autonomy for diabetes care. 16 Similarly, higher maternal depressive symptoms have been found to be associated with poorer youth diabetes adherence.…”
Section: Familymentioning
confidence: 99%
“…16 Similarly, higher maternal depressive symptoms have been found to be associated with poorer youth diabetes adherence. 39 Researchers suggested that the maternal depression symptoms may impede the ability of mothers to facilitate their youth's self-management skills over time. 39 …”
Section: Familymentioning
confidence: 99%
See 1 more Smart Citation